Kelayakan Usaha Mie Badhogak Pada Umk Mina Sejahtera - Dian Iriani; Aprillia Anggita Simanullang; Tiara Ariza (Peneliti.net, 2022)
Mina Sejahtera UMK is a company or home industry engaged in fish processing in Pulau Lawas village. One of its products is badhogak fish noodles. Problems that arise from packaging, product marketing, and bookkeeping in production activities. The purpose of this service is to improve the quality of packaging on Sunti Sukaku products, especially badhogak noodles, to improve labeling quality, to increase marketing both online and offline, to minimize expenses and maximize income with good business management, and to improve the feasibility of the badhogak noodle business. The results of the feasibility study for the badhogak noodle business at Mina Sejahtera UMK went well and as planned. These activities include the manufacture of Sunti Sukaku products, packaging of Sunti Sukaku products, labeling of Sunti Sukaku products, the marketing of Sunti Sukaku products, making bookkeeping or financial management formats for Mina Sejahtera MSEs to be able to continuously monitor expenses and income obtained from product sales so that they can know the expenses and income of this Badhogak noodle business. Hopefully in the future, UMK Mina Sejahtera could be a big industry with high income